(untitled) (ItalianoLinguadue, 2020)
Il seguente articolo analizza una prova di ascolto di italiano LS di livello C1, apparsa nella sessione invernale 2016 della certificazione CILS (Università per Stranieri di Siena). L’analisi è condotta su più campioni, sia di apprendenti di italiano [di livello C1 (n=70) e di livello B1 (n=67)] che di nativi [liceali (n=88) ed esperti (n=62)]. L’esito della ricognizione attesta criticità di diverso genere. Investigation into the validity of a CILS level C1 listening test This paper deals with a test C1 level listening which appeared in the 2016 winter session of CILS Certificate (University for Foreigners, Siena). The study refers to different populations, including both students of Italian as a FL [C1 level (n=70) and B1 level (n=67)] and natives [students at secondary School (n=88); highly proficient natives (n=62)]. Our analysis detects different problems.